2014
DOI: 10.5530/pc.2014.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Effects of Peganum Harmala L. Root Extract on Isolated Rat small Intestine

Abstract: Background: Peganum harmala L. is a medicinal plant used in Jordan and in many countries in traditional medicine against several diseases, including gastrointestinal disorders. Objective: In this study, the effects of crude ethanolic root extract of P. harmala on the isolated smooth muscle of the rat jejunum intestine were investigated. Materials and Methods: The isolated organ bath method was adopted. The efficacy was recorded and analyzed by biological signal collection and analysis recording. Results: The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It has been reported that Peganum harmala exerts broad pharmacological effects such as amelioration of cardiovascular, gastrointestinal and respiratory problems, as well as possessing antioxidant, antimicrobial, antiviral, antihelmintic, antifungal, antineoplastic properties and pain-relieving potential [5,6]. In previous studies, the anti-spasmogenic activities of ethanolic extract of P. harmala and its alkaloids on intestinal SMCs, were demonstrated [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Peganum harmala exerts broad pharmacological effects such as amelioration of cardiovascular, gastrointestinal and respiratory problems, as well as possessing antioxidant, antimicrobial, antiviral, antihelmintic, antifungal, antineoplastic properties and pain-relieving potential [5,6]. In previous studies, the anti-spasmogenic activities of ethanolic extract of P. harmala and its alkaloids on intestinal SMCs, were demonstrated [7,8].…”
Section: Introductionmentioning
confidence: 99%